Effectiveness of vaccination in reducing hospitalization and mortality rates in dialysis patients with Omicron infection in China: A single-center study - Quanchao Zhang; Caibao Lu; Hongwei Chen; Moqi Li; Xiaoxin Bai; Jing Chen; Danni Li; Yuesha Zhang; Na Lei; Wenchang He; Yiqin Wang; Jinghong Zhao; et al. (Taylor & Francis Group, 2023)
The impact of vaccination on the outcomes of dialysis patients with Omicron infections in China remains unknown. This study aimed to examine the relationship between vaccination and hospitalization as well as all-cause mortality. We included patients who had undergone maintenance hemodialysis (HD) for at least three months at our center. The follow-up period spanned from December 2022 to February 2023. We assessed the connections between vaccination and hospitalization as well as all-cause mortality using univariable and multivariable logistic regression models. Receiver operating characteristic (ROC) curves were used to assess the diagnostic accuracy for hospitalization and all-cause mortality. Ultimately, a total of 427 HD patients with confirmed SARS-CoV-2 infections were included. The patients had a mean age of 54 years, and 59.4% of them were male. Prior to the investigation, 108 patients had received vaccinations, with 81 of them having completed or received booster vaccinations. Throughout the follow-up period, 81 patients were admitted to the hospital, and 39 patients died. Multivariable logistic regression revealed that vaccination significantly decreased all-cause mortality (OR 0.25, 95% CI 0.07-1.94, P = .04). Moreover, completed or booster vaccinations were effective in reducing the hospitalization rate (OR 0.41, 95%CI 0.17-0.99, P = .047). It is noteworthy that both unvaccinated and vaccinated individuals experienced mild symptoms, and the hospitalization rates were relatively low in both groups. Despite the reduced pathogenicity of Omicron compared to previous strains in dialysis patients, both vaccinated and unvaccinated, vaccination still provides benefits for improving the prognosis.